Factors associated with student achievement in the English learning process at the Tercer Ciclo de Educación Básica, del Centro Escolar Comunidad Pradera III” at Ciudad Delgado, San Salvador, year 2015 - Claros González, Josue Ramón
Learning English is not as easy as some people say, especially for teens that have never been exposed to it (Locher, 2008). According to Savignon (1972) cited by Omaggio (2001) having the power of speaking a foreign language means having the ability of communicating everywhere. The English language is taught as a compulsory subject for a period of five years, at public schools in El Salvador, as it is established in the 2021 National Education Plan, by the Ministry of Education (2008). It is taught since the seventh grade until high school with a class time of three hours per week. In El Salvador the English study program is developed in three class hours per week. A study year, according to the Ministry of Education, has 40 weeks; making a total of 120 class hours in those 40 weeks during the study year and 600 class hours since the seventh grade to high school. This study was carried out to find out the factors that were affecting the process of learning English. Some of those factors were pointed out through this research. They were kids’ family context, kids’ school life and violence and crime in the kids’ eighborhood. It is important for teachers to know those factors that do not let students to learn the language so that they can try to overcome such issue. For that reason, the research topic for this study was Factors associated with student achievement in the English learning process at the Tercer Ciclo de Educación Básica, del Centro Escolar “Comunidad Pradera III” at Ciudad Delgado, San Salvador, year 2015.